Rubia akane regulates process of NASH in Choline-deficient, L-amino acid-defined, high-fat diet-fed mice - Nam, Yunseong; Erdenebileg, Saruul; Kim, Myung Suk; Park, Sun Young; Kim, Min Jeong; Zolzaya Bayarsukh; JeonKiBeom; ParkSiEun; Nho, Chu Won (2023 KSBMB Winter Workshop, 2023)
Non-alcoholic fatty liver disease (NAFLD) ranges in severity from hepatic steatosis to cirrhosis due to fat accumulation. It is also known that the chances of recovering from nonalcoholic steatohepatitis (NASH) decrease dramatically in the developed fibrosis stage. The root of Rubia akane (RA) is a medicinal plant that has been traditionally used as antimicrobial and hemostasis. However, their therapeutic effects on NASH are unknown. In this study, we investigated the effects of RA 95% ethanol extract on NAFLD and liver fibrosis and elucidated their mechanisms. Palmitic acid-treated HepG2 cells indicated lipid accumulation and C57BL/6J mice fed a Choline-deficient, L-amino acid-defined, high-fat diet (CDAHFD) were induced to exhibit symptoms of NASH and fibrosis. Oral administrated RA extract decreased level of malondialdehyde, lipid peroxidation marker, in liver. In addition, RA extract alleviated the oxidative stress, fatty acid oxidation, and fibrosis-related gene expression such as Cat, Sod1, Ppara, Col1a1 in the liver tissue. These results suggest RA extract might have inhibitory effects of NASH in CDAHFD fed mouse model by decreasing oxidative stress and fibrosis-related markers.